ENGLISH THEMATIC INTEGRATED LEARNING BOOK BASED ON LOCAL CONTENT FOR JUNIOR HIGH SCHOOL IN TRENGGALEK - Arini Dwi Agus Bintari Ningrum (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2020)
The research design is educational Research and Development as one research design aimed at developing educational products, like curriculum, syllabus, textbooks, instructional media, etc. The sample of this research was seventh grade in Junior High School 3 Trenggalek 2019/2020 academic year that consists of 26 students from the G class and 24 students from the H class. The instruments used in this research are questionnaires and interviews. The data collected by questionnaires is analyzed quantitatively way, and data collected by interviews are analyzed qualitatively way. The result is Sig. (2-tailed) of 0.000 < 0.05, it can be concluded that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant difference between the average student learning outcomes in the experimental and control groups. The result of field testing was 1738 that means the respondent agrees that the product of this research was very good and flexible to use as media in learning vocabulary. So, My Menaksopal as the product of this research is an effective learning media for junior high school students. This product help student in learning English because it related to the student’s daily activity.